Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972 - Christodoulou, Magdalini; Kihara, Terue Cristina (Zootaxa, 2018)
Atyaephyra stankoi’s Karaman 1972 syntypic material has been assumed to be lost. However, M. Karaman’s type material has been found within the zoological collections of the University of Novi Sad, Serbia and thus a lectotype is herein designated, while placing aside the designated neotype. An updated distribution of A. stankoi in Greece and F.Y.R.O.M. is provided based on field collections and literature data, while support is provided by COI data. Furthermore, new records in Peloponnesus and Attica expand the known distribution of species in Greece. Finally some preliminary insights are given on the species zoogeography, while there seems to be a correspondence between genetic haplotype groups and geographical location.